Wintering areas of Great SkuasStercorarius skuabreeding in Scotland, Iceland and Norway - Magnusdottir, E.; Leat, E.H.K.; Bourgeon, S.; Strøm, H.; Petersen, A.; Phillips, R.A.; Hanssen, S.A.; Bustnes, J.O.; Hersteinsson, P.; Furness, R.W. (Bird Study, 2012)
Capsule Great Skuas Stercorarius skua breeding in Scotland, Iceland, and Norway, winter in different areas. Aims To assess the winter distribution of adult Great Skuas breeding in different countries. Methods Geolocation data-loggers were deployed on breeding adults at colonies in Shetland (Scotland), southeast Iceland, and Bjørnøya (Norway) in 2008. Loggers were recovered when birds returned to breed the next year and downloaded data were processed to indicate the location of each individual throughout the winter period. Results Adult Great Skuas from Scotland wintered off northwest Africa and southern Europe. Adults from Iceland mostly wintered off Canada, with small numbers visiting northwest Africa and Europe. Although adults from Bjørnøya (Norway) migrated to similar areas to birds from Iceland, a slightly greater proportion wintered off Europe, and most used areas further north than birds from Scotland. Although three birds studied over consecutive winters used the same small area in consecutive years, four moved between different areas within one winter. Conclusion Great Skuas show clear variation in migrations among breeding regions, and some evidence of individual consistency.